2013
DOI: 10.1144/petgeo2011-004
|View full text |Cite
|
Sign up to set email alerts
|

Geologically-based permeability anisotropy estimates for tidally-influenced reservoirs using quantitative shale data

Abstract: The effect of the vertical to horizontal permeability ratio ( k v  / k h ) on many displacement properties is significant, making it an important parameter to estimate for reservoir models. Simple ‘streamline’ models have been developed which relate k v  / k h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…The permeability ratio (horizontal vs. vertical permeability) also increases with stress due to greater burial depth (Adams et al, 2013). Because permeability is the key parameter controlling fluid flow in reservoir rocks, measuring and understanding anisotropic permeability is of great significance for modelling oil and gas flow in petroleum reservoirs (Burton and Wood, 2013). It may also be useful for understanding groundwater flow (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The permeability ratio (horizontal vs. vertical permeability) also increases with stress due to greater burial depth (Adams et al, 2013). Because permeability is the key parameter controlling fluid flow in reservoir rocks, measuring and understanding anisotropic permeability is of great significance for modelling oil and gas flow in petroleum reservoirs (Burton and Wood, 2013). It may also be useful for understanding groundwater flow (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although economic shale gas production has been achieved through horizontal drilling and multistage hydraulic fracturing, shale reservoir permeability is still one of the critical parameters in the evaluation of a shale gas play and the understanding of its gas flow and production behaviour. Laboratory measurement using core samples is an important means of obtaining anisotropic permeability information (Burton and Wood, 2013). However, such measurements of shale permeability often use core samples that were drilled vertically, and hence, measure only the vertical permeability of the reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, fluid flow direction depends on both pressure gradient and the principal directions of anisotropy. Several studies have shown the existence of anisotropy in the shale formations (McCarthy 1991;Ayan et al 1994;Kwon et al 2004;Burton 2011). In fact, anisotropy exists in the scale of micrometer or nanometer under microstructural observations using transmission electron microscopy (TEM) (Kwon et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Burton & Wood () provided quantified assessments of the thickness and lateral distribution of mud beds in tidally influenced reservoirs. From the standpoint of reservoir heterogeneity, the ‘shale length’ (i.e.…”
Section: Introductionmentioning
confidence: 99%